2013
DOI: 10.1371/journal.pntd.0002076
|View full text |Cite
|
Sign up to set email alerts
|

HLA-A2 and B35 Restricted Hantaan Virus Nucleoprotein CD8+ T-Cell Epitope-Specific Immune Response Correlates with Milder Disease in Hemorrhagic Fever with Renal Syndrome

Abstract: BackgroundHantaan virus (HTNV) infection in humans is a serious public health concern in Asia. A potent T cell activation peptide vaccine from HTNV structure protein represents a promising immunotherapy for disease control. However, the T cell epitopes of the HTNV restricted by the HLA alleles and the role of epitope-specific T cell response after HTNV infection remain largely unexplored.Methodology/Principal FindingsFive well-conserved novel CD8+ T-cell epitopes of the HTNV nucleoprotein restricted by the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 39 publications
3
55
0
Order By: Relevance
“…Likewise, a recent HTNV study also showed that the frequency of the epitopespecific pentamer + CD8 + T cells was statistically higher in the early stage than that in the late stage (7). Further longitudinal analysis of the virus-specific T cell responses, however, was not available for measuring the discrepancy.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Likewise, a recent HTNV study also showed that the frequency of the epitopespecific pentamer + CD8 + T cells was statistically higher in the early stage than that in the late stage (7). Further longitudinal analysis of the virus-specific T cell responses, however, was not available for measuring the discrepancy.…”
Section: Discussionmentioning
confidence: 97%
“…The protective immune responses elicited by the nucleocapsid protein are thought to be mainly cellular, since nucleocapsidspecific antibodies are neither neutralizing nor protective. In HFRS, most epitopes identified to date are on the nucleocapsid protein of HTNV and Puumala virus (PUUV) (5,7,13,14,17). Therefore, nucleocapsid protein seems an attractive target of hantavirus-specific immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess HTNV-specific responses, HTNV NP 9-mer peptide pools were used to stimulate the PBMCs of HFRS patients in vitro during the early phase. The peptide pools contained 14 peptides that were confirmed to be HTNV NP CTL epitopes in our previous study (14)(15)(16). Detailed information regarding the 14 epitopes can be found in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…From these studies it has been hypothesized that the strong CD8+ T-cell responses will eliminate virus, but that such intensive T-cell responses might also result in an excessive amount of cytokines, which promote capillary leakage and endothelial cell dysfunction [69,73]. In contrast to these findings, a recent study of HFRS patients shows that the prevalence of N-antigen-specific CD8+ T cells correlated with the early, acute stages of infection and declined thereafter [83]. Hence, the CD8+T cells would be expected to have a protective effect rather than promote immune pathology.…”
Section: Differential Immune Responses In Rodents and Humansmentioning
confidence: 99%